Cross-Sectional Study in a Large Cohort of Chinese Patients With GJB1 Gene Mutations - Liu, Xiaoxuan; Duan, Xiaohui; Zhang, Yingshuang; Sun, Aping; Fan, Dongsheng (Frontiers in Neurology, 2020)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous group of inherited neuropathies. The GJB1 gene is the pathogenic gene of CMTX1. In this study, we screened a cohort of 465 unrelated Chinese CMT patients from years 2007 to 2019 and 650 controls by direct Sanger sequencing in GJB1 gene or targeted next-generation sequencing (NGS) or whole-exome sequencing (WES). A bidirectional Sanger sequencing would be performed on the 600 bases in the upstream promoter region and 30 bases in the 3′ untranslated region (UTR), if no mutation was found in the coding region of GJB1 of the patient. According to the results, 24 missense mutations, 4 nonsense mutation, 1 entire deletion, 1 intronic mutation, and 4 frameshift mutations in GJB1 were identified. Three of them were novel mutations (c.104 T>C, c.658-659 ins C, and c.811 del G). Moreover, central nervous system involvement was observed in five patients carrying mutations of R15W, V95M, R142W, R164W, and E186K. Our findings expand the mutational spectrum of the GJB1 gene in CMT patients. We also explored the genotype–phenotype correlation according to the collected information in this study. NGS panels for detecting inherited neuropathy should cover the non-coding region of GJB1.